Prevalence and distribution of acute gastrointestinal illness in the community of China: a population-based face-to-face survey, 2014-2015 - Jikai Liu; Baozhang Luo; Yijing Zhou; Xiaochen Ma; Junhua Liang; Xianglai Sang; Le Lyu; Wen Chen; Pengyu Fu; Hong Liu; Shiqi Zhen; Chao Wang; et al. (BMC, 2023)
Abstract Background The true incidence of acute gastrointestinal illness in China is underrecognized by surveillance systems. The aims of this study were to estimate the incidence and prevalence of self-reported AGI in the community of China, and to investigate sociodemographic and epidemiological determinants of AGI. Methods We conducted a 12-months cross-sectional population-based survey in eight provinces of China during 2014-2015. The survey determined the prevalence and incidence of acute gastrointestinal illness (AGI) in the total permanent resident population in China according to the census of the population in 2010. The random multilevel population sample was stratified by geographic, population, and socioeconomic status. We used a recommended case definition of AGI, with diarrhea (three loose or watery stools) and/or any vomiting in a four-week recall. A face-to-face survey was conducted by selecting the member in the household with the most recent birthday. Results Among 56,704 sampled individuals, 948 (1,134 person-time) fulfilled the case definition; 98.5% reported diarrhea. This corresponds to 2.3% (95% CI:1.9%-2.8%) of an overall standardized four-week prevalence and 0.3 (95% CI: 0.23-0.34) episodes per person-year of annual adjusted incidence rate. There was no significant difference between males and females. The incidence rates were higher among urban residents, and in the spring and summer. In the whole study period, 50% of the cases sought medical care, of which 3.9% were hospitalized and 14.3% provided a biological sample for laboratory identification of the causative agent. Children aged 0-4 and young adults aged 15-24, people living in rural areas and people who traveled frequently had higher prevalence of AGI. Conclusion Results showed that AGI represents a substantial burden in China, and will contribute to the estimation of the global burden of AGI. Complemented with data on the etiologies of AGI, these estimates will form the basis to estimate the burden of foodborne diseases in China.